Retracted: Promosi Kesehatan Gigi Dengan Menggunakan Media Leaflet Terhadap Pengetahuan, Sikap Dan Status Kebersihan Gigi Dan Mulut Siswa Sekolah Dasar Kota Kupang - Melkisedek O. Nubatonis (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2017)
This article has been retracted at the request of the Editor in Chief of the Jurnal Info Kesehatan volume 15 number 2 of 2017 pages 451-468 because it has been published again in the Jurnal Kesehatan Gigi volume 6 number 2 year 2019 pages 147-156 with DOI: 10.31983/jkg.v6i2.5493. Papers submitted to Jurnal Info Kesehatan should neither published again previously nor be under consideration for publication another journal. Therefore, the author should make a statement upon submitting. Reusing data in any form must follow good citation principles, therefore this paper has ethical violations in the scientific publishing system. Notice of the revocation of